2005
DOI: 10.1002/pd.1088
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of megacystis‐microcolon‐intestinal hypoperistalsis syndrome: contribution of amniotic fluid digestive enzyme assay and fetal urinalysis

Abstract: For the first time, we propose a prenatal diagnosis of MMIHS based on amniotic fluid digestive enzyme assay and on fetal urinalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…MMIHS can be prenatally diagnosed on the basis of amniotic fluid digestive enzyme and fetal urinalysis. 18 Biochemical fetal urine analysis can also be used to rule out a fistula between the urinary and digestive tracts. 19 In conclusion, LUTO is the main etiology of megacystis.…”
Section: Discussionmentioning
confidence: 99%
“…MMIHS can be prenatally diagnosed on the basis of amniotic fluid digestive enzyme and fetal urinalysis. 18 Biochemical fetal urine analysis can also be used to rule out a fistula between the urinary and digestive tracts. 19 In conclusion, LUTO is the main etiology of megacystis.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated renal hydronephrosis preceded the development of megacystis in a subset of reported cases [14,15,27,28] including our own prenatally diagnosed case. As such, isolated bilateral hydronephrosis may be an early marker of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Given urinary analyte profiles indicating preserved renal function in MMIHS cases undergoing vesicocentesis [28], there does not appear to be a clear indication for prenatal vesicocentesis or vesicoamniotic shunt placement. These findings are further supported by the fact that MMIHS is rarely associated with significant renal impairment at birth.…”
Section: Discussionmentioning
confidence: 99%
“…These analytes suggest fetal vomiting of bile and intestinal contents containing digestive enzymes. Fetal urinalysis was normal except for high calcium levels (>0.6 mmol/l) in all cases [12]. With these predictive valves, amniotic fluid analysis may be considered as an adjuvant investigation for accurate diagnosis and may be warranted for optimal prenatal counseling.…”
Section: Discussionmentioning
confidence: 99%
“…As MMIHS involves bowel and urinary systems in the fetus, some investigators have studied amniotic fluid digestive enzymes and fetal urine biochemistry as a predictor of this condition. Analysis has shown that an abnormal amniotic fluid digestive enzyme profile characterized by γ-glutamyl transpeptidase and aminopeptidase M ≥99th percentile associated with normal intestinal alkaline phosphatase levels were observed in the majority of cases with 80% sensitivity and 89% specificity for prediction of this condition when compared to controls [12]. These analytes suggest fetal vomiting of bile and intestinal contents containing digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%